Accidental bequests: A curse for the rich and a boon for the poor - Helmuth Cremer; Firouz Gahvari; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2010)
When accidental bequests signal otherwise unobservable individual characteristics such as productivity and longevity, the tax administration should partition the population into two groups: One consisting of people who do not receive an inheritance and the other of those who do. The first tagged group gets a second-best tax à la Mirrlees; the second group a first-best tax schedule. The solution implies that receiving an inheritance makes high-ability types worse off and low-ability types better off. High-ability individuals will necessarily face a bequest tax of more than 100%, while low-ability types face a bequest tax that can be smaller as well as larger than 100% and may even be negative.
Keywords: H21; 330; accidental bequests; estate tax; tagging; first best; second best; Grundsteuer; Erbschaftsteuer; Optimale Besteuerung; Erbe; Verteilungswirkung; Theorie